Coherent mid-infrared supercontinuum generation with As2Se3 photonic crystal fiber and femtosecond Airy pulses. (18th November 2015) - Yuan, Wu
Abstract: We discuss a novel method for generating hyper-broadband mid-infrared (MIR) supercontinua (SC) with coherent bandwidth from ~2 μ m to ~10 μ m by using As2 Se3 photonic crystal fiber (PCF) and a 4.1 μ m pump with femtosecond (fs) Airy pulse profile. Our simulations confirm that, when pumping in the normal dispersion region, the deceleration and self-healing properties of the Airy pulse can suppress the incoherent noise in modulational instability (MI) induced SC generation and maintain the pulse coherence over a long propagation distance. We also find that fs Airy pulse can generate an MIR SC with a broader coherent bandwidth than these can be achieved with fs parabolic secant pulse.